Optimering av Ventildiagnostik på Preem AB:s raffinaderi i Lysekil - Johansson, Andreas; Wallberg, Josefin (My University, 2025)
This report investigates how valve diagnostics at Preem AB’s refinery in Lysekil can be optimized to increase productivity and improve maintenance efficiency. The focus is on analyzing the current valve diagnostic system, where the positioner DVC6200 with AD-level (Advanced Diagnostics) is used in combination with a centralized system called AMS (Asset Management System). The report identifies the benefits of utilizing PD-level diagnostics (Performance Diagnostics), which is not currently used at the refinery. The results show that PD-level allows for continuous monitoring of the control valve condition, leading to early fault detection and reduced risk of operational disturbances. The implementation of PD-level diagnostics can be easily done via a USB drive, without disrupting the engineers’ daily tasks. The economic benefits include more efficient resource planning, minimization of production losses, and better utilization of the workforce. It has also been shown that the new diagnostics can detect previously unknown valve faults, reducing undetected faults from 15% to 10%. This results in long-term savings through the implementation of diagnostics and provides positive economic effects for Preem. Environmental benefits are also highlighted, including reduced energy consumption and lower valve leakage, supporting Preem’s sustainability goals. The report also discusses the possibilities with the new positioner (DVC7K), which offers improved diagnostics, better user interface, and extended lifespan. Furthermore, the importance of diagnostics for maintaining the Safety Integrity Level (SIL) of the control valves’ safety function (SIF) is addressed, which is ensured through regular proof testing during planned shutdowns. Finally, the results are compared with another industrial operation, where the implementation of PD-level diagnostics led to improved maintenance shutdown planning and more efficient process flows.
Keywords: Preem AB; DVC6200; Advanced Diagnostics; AMS system; Performance Diagnostics; Economic benefits; Sustainability; DVC7K; Safety Integrity Level (SIL)